2017
DOI: 10.1208/s12248-017-0071-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of a PK-PD Modeling and Simulation-Based Strategy for Clinical Translation of Antibody-Drug Conjugates: a Case Study with Trastuzumab Emtansine (T-DM1)

Abstract: Successful clinical translation of antibody-drug conjugates (ADCs) can be challenging due to complex pharmacokinetics and differences between preclinical and clinical tumors. To facilitate this translation, we have developed a general pharmacokinetic-pharmacodynamic (PK-PD) modeling and simulation (M&S)-based strategy for ADCs. Here we present the validation of this strategy using T-DM1 as a case study. A previously developed preclinical tumor disposition model for T-DM1 (Singh and Shah, AAPSJ. 2015; 18(4):861… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…The authors state that this model suggested that a fractionated dosing regimen may provide improved efficacy with trastuzumab emtansine. It was concluded that this modeling and simulation strategy for ADC pharmacokinetics/pharmacodynamics was capable of predicting the clinical efficacy of ADCs a priori and the authors were able to retrospectively validate this strategy for all clinically approved ADCs [78]. …”
Section: Trastuzumab Emtansinementioning
confidence: 99%
“…The authors state that this model suggested that a fractionated dosing regimen may provide improved efficacy with trastuzumab emtansine. It was concluded that this modeling and simulation strategy for ADC pharmacokinetics/pharmacodynamics was capable of predicting the clinical efficacy of ADCs a priori and the authors were able to retrospectively validate this strategy for all clinically approved ADCs [78]. …”
Section: Trastuzumab Emtansinementioning
confidence: 99%
“…Going forward we plan to translate this systems PK-PD to predict bystander effect of ADCs in the clinic (Shah et al, 2012;Betts et al, 2016;Singh and Shah, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…The final systems PK-PD model was used to evaluate the effect of different dosing regimen and tumor composition on the bystander effect of ADC. The presented PK-PD model could be translated to predict the bystander effect of ADCs in the clinic using the strategies presented by us before (Shah et al, 2012;Singh and Shah, 2017a).…”
Section: Downloaded Frommentioning
confidence: 99%
See 2 more Smart Citations